Adolescents' Sexual Encounters With Either Romantic or Casual Partners and the Quality of Their Romantic Relationships Four Years Later. Issue 2 (12th February 2020) - Shulman, Shmuel; Scharf, Miri; Ziv, Ido; Norona, Jerika; Welsh, Deborah P.
Abstract : Adolescent sexual behavior was examined within a health perspective. Assuming a developmental perspective, the current study investigated the associations between sexual behavior in either stable relationships or in casual encounters, and the quality of romantic relationships and affect 4 years later. Data were collected from 144 Israeli adolescents aged 16–18 years (mean age 16.57 years). Participants completed diary data over a period of 10 days and reported on the quality of their romantic encounters and their emotions, and on their sexual behavior in stable relationships or casual encounters. Four years later, they were asked to complete diary data again for 10 consecutive days and report on the quality of their romantic relationships and their positive and negative affect. Findings indicate that involvement in sexual behavior in stable romantic relationships was associated only with future romantic partner support. In contrast, earlier involvement in casual sexual behavior was associated with a number of future indices: lower partner support, greater negative affect as well as greater relationship tension, and dyadic hurtful behavior 4 years later. The differential role of sexuality within a stable relationship or casual encounters among adolescents for their future romantic development is discussed within a developmental framework.